Geoffrey James : the Lethbridge Project - Doyon, Jacques (CV Photo)

(untitled) (Les Productions Ciel variable, 2000)
Summary The Lethbridge Project looks at both the city and nature, and at their transformations. Geoffrey James evokes the way in which landscape, whether in the heart of the city or in the suburbs, is inhabited and arranged. He then relates the circumstances, both deliberate and chance, that brought him to produce his previous photographic projects about cultural landscapes.